New findings on the effects of the İzmit Mw=7.4 and Düzce Mw=7.2 earthquakes - Güney, C.; Ozludemir, M. T.; Celik, R. N.; Kutoglu, H. S. (Copernicus Publications, 2011)
The 17 August 1999 İzmit Mw=7.4 and the 12 November 1999 Düzce Mw=7.2 earthquakes caused a 150 km long surface rupture in the western part of the North Anatolian Fault. The coseismic slips along the fault line and the trace of the surface ruptures were studied in detail in Barka (1999), Reilinger et al. (2000), Cakir et al. (2003a, b) and Ergintav (2009) after the earthquakes. However, the basin to the east of Sapanca Lake was a black hole for all investigations because there was no geodetic network and no significant deformation that could be obtained by using InSAR techniques. In this study, findings on the abovementioned basin have been reinterpreted through a GPS network newly explored. This interpretation shows coseismic slips of between 2–3 m, and links the surface rupture to the main branch of the North Anatolian Fault (NAF) in the east Sapanca basin.
Keywords: Environmental sciences; QE1-996.5; Geography. Anthropology. Recreation; GE1-350; Geology; Environmental technology. Sanitary engineering; TD1-1066